Nasal Chondromesenchymal Hamartoma: Rare Case Report in an Elderly Patient and Brief Review of Literature - Kanish Mirchia; Rana Naous (Case Reports in Pathology)
Hamartomas are considered a mixture of nonneoplastic tissue, which may be indigenous to a different location in the body. As such, they may be epithelial, mesenchymal, or mixed. In the sinonasal region, the following hamartomatous lesions are considered to lie on a spectrum and include respiratory epithelial adenomatoid hamartoma (REAH), chondro-osseous respiratory epithelial adenomatoid hamartoma (COREAH), and nasal chondromesenchymal hamartoma (NCMH). To our knowledge, less than 50 cases of sinonasal hamartomas have been reported in the English literature so far with NCMH being very rare and primarily a tumor in infancy, with only 2 cases reported in individuals older than 16 years of age. We report a highly unusual case of a NCMH in the right maxillary sinus of a 70-year-old female.